Strategi Komunikasi Efektif Untuk Meningkatkan Partisipasi Masyarakat Pedesaan dalam Pembangunan Desa: Sebuah Kajian Literatur - Nurhasanah, Sabrina; Nurlina, Lilis; Yunasaf, Unang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This article discusses effective communication strategies to increase rural community participation in village development. Through a literature review, this article attempts to provide a thorough understanding of how effective communication strategies can help accelerate the process of village development. This article will also cover some important points such as the characteristics of rural communities, the role of communication in rural development, forms of communication in rural communities, and communication strategy factors. Rural communities are characterized by living in groups, most of the communities have similar interests. Development communication has a crucial role in the process of village development. Villagers like to talk directly, communicators can take advantage of this by approaching villagers directly. Delivering messages while villagers are doing their activities such as during gotong royong, village meetings and so on. The best way to convey communication is that there are five important communication components to consider, namely the communicator, Message, Channel, Communicator, Effect. In implementing an effective communication strategy, it is necessary to pay attention to the characteristics of the village community, the role of communication in village development, the form of village community communication, and communication strategy factors.